2014
DOI: 10.3389/fphar.2014.00087
|View full text |Cite
|
Sign up to set email alerts
|

Assessing analytical methods to monitor isoAsp formation in monoclonal antibodies

Abstract: A ubiquitous post-translational modification observed in proteins is isomerization of aspartic acid to isoaspartic acid (isoAsp). This non-enzymatic post-translational modification occurs spontaneously in proteins and plays a role in aging, autoimmune response, cancer, neurodegeneration, and other diseases. Formation of isoAsp is also a significant issue for recombinant monoclonal antibody based protein therapeutics particularly when isomerization occurs in a complementarity-determining region due to potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 36 publications
(46 reference statements)
0
35
0
Order By: Relevance
“… 21 Protein-based bioconjugates represent an increasingly popular choice for pharmaceuticals, 22 , 23 accentuating the need for better understanding of effective protein lifetime and degradation byproducts. For example, perturbations to complementarity-determining regions (CDRs) of antibodies can drastically reduce antigen binding efficacy, 24 as demonstrated by deactivation of monoclonal immunoglobulin γ2 following a single isomerization. 25 Furthermore, deamidation is facilitated by the solvent exposed and flexible nature of CDRs.…”
mentioning
confidence: 99%
“… 21 Protein-based bioconjugates represent an increasingly popular choice for pharmaceuticals, 22 , 23 accentuating the need for better understanding of effective protein lifetime and degradation byproducts. For example, perturbations to complementarity-determining regions (CDRs) of antibodies can drastically reduce antigen binding efficacy, 24 as demonstrated by deactivation of monoclonal immunoglobulin γ2 following a single isomerization. 25 Furthermore, deamidation is facilitated by the solvent exposed and flexible nature of CDRs.…”
mentioning
confidence: 99%
“…Previous reports have shown that an isoAsp-containing peptide elutes earlier than the corresponding Asp-containing peptide when separated by RP chromatography as a result of changes to the local protein structure. 3,17,25 Intact mass analysis of these 2 elution peaks revealed that the corresponding peptides had the same mass (Fig. 2).…”
Section: Characterization Of Asp Isomerization In Mab1mentioning
confidence: 93%
“…2,12,13 Accelerated stress conditions coupled with various analytical methods have been described to generate, isolate, and characterize Asp isoforms to understand developability risks. 9,10,[14][15][16][17][18] The most common approach for identifying and quantifying Asp isomerization in a mAb involves enzymatic digestion of accelerated stress samples, separation of peptides by reversed phase (RP) liquid chromatography, and subsequent characterization by mass spectrometry.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve better resolution and more accurate quantitation, molecules can be broken into their subunits before separation, such as cleaving antibodies into (Fab) 2 and Fc. 36,37 This subunit approach nevertheless is molecule-specific and often requires extensive method development and optimization to achieve desired outcome, adding significant burden to analytical development. An alternative approach to these methods is tryptic peptide mapping (TPM) by LC coupled with MS that can be extremely powerful in probing protein PTMs as it provides comprehensive information on deamidation, oxidation, isomerization, glycan profiles, etc.…”
Section: Introductionmentioning
confidence: 99%